Biosci. J. 2017
DOI: 10.14393/bj-v33n1a2017-34668
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temporary cements on the bond strength of a resin cement to a pre-hybridized dentin

Abstract: This study assessed the bond strength of a resin cement when Immediate Sealed Dentin (ISD) was contaminated by different temporary cements applying a microshear test. Forty-eight fragments of third molar crowns were mounted in acrylic resin and worn until the dentin was exposed. The substrates were sealed with a 3-step conventional adhesive system and divided into four groups (n=12): Control (without temporary cement) and three groups that used different temporary cements -Provy, RelyX Temp NE, and Provitem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“… The study supported the use of IDS which contributed to the high success rate in terms of debonding (2%). Lima et al 2017 145 In vitro Bond strength Assessed the bond strength of a resin cement (RelyX ARC) when IDS (Adper Scotchbond Multi-Purpose) was contaminated by different temporary cements (Provy/RelyX Temp NE/Provitemp). Provitemp temporary cement sealing increased microshear bond strength of the resin cement on dentin treated with IDS.…”
Section: Resultsmentioning
confidence: 99%
“… The study supported the use of IDS which contributed to the high success rate in terms of debonding (2%). Lima et al 2017 145 In vitro Bond strength Assessed the bond strength of a resin cement (RelyX ARC) when IDS (Adper Scotchbond Multi-Purpose) was contaminated by different temporary cements (Provy/RelyX Temp NE/Provitemp). Provitemp temporary cement sealing increased microshear bond strength of the resin cement on dentin treated with IDS.…”
Section: Resultsmentioning
confidence: 99%
“…Resin temporary cement would plug the dentinal tubules, interfering with subsequent adhesive penetration [3,25]. However, this article concluded that the resin-based temporary cement had no significant effect on bond strength with moderate intragroup heterogeneity, most likely due to the exceptional research by Lima [16].…”
Section: Discussionmentioning
confidence: 88%
“…In the DDS subgroup, after removing Fiori-Júnior [ 22 ], the overall I 2 decreased to 51%. In the resin temporary cement subgroup, after omitting Lima [ 16 ], there was a decline in intragroup heterogeneity ( I 2 from 68 to 56%) and swift of effect ( Z -test p from 0.11 to 0.007), leading to an 8% drop of overall I 2 . The altered result was that resin temporary cement lowered the bond strength by − 0.73 MPa (95% CI = − 1.26 to − 0.2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations